PERIODONTAL STATUS IN PATIENTS WITH MANDIBULAR FRACTURES - Rosen Tsolov; Elena I. Firkova (Peytchinski Publishing, 2022)
Purpose: The aim of the present study was to assess the gingival and periodontal status of patients with maxillofacial trauma and to determine the need for periodontal treatment after removal of the intramaxillary fixation. Material and methods: The study included 36 patients with a fracture of the lower jaw. After the clinical and radiological examination of the patients, treatment was performed on a case-by-case basis. 30 days after fixation and removal of the wire ligatures of the patients, the oral-hygienic and periodontal status was assessed using the following indices: simplified oral hygiene index, gingival bleeding index, community periodontal index of treatment needs and evaluation of oral malodour. Results: The most common cause of fractures is a traffic accident, followed by domestic injuries. The level of oral hygiene immediately after removal of the wire ligatures and intermaxillary fixation varied between relatively good and poor, with a greater number of patients having poor hygiene (OHI-S ≥5). The periodontal status of the patients, measured by CPITN, also showed a statistically significant level of clinically established periodontal destruction. Halitosis was detected in all patients. Conclusions: The course of the healing process in the alveolar bone and the functional rehabilitation of patients with mandibular fractures depends not only on the type of surgical treatment for immobilization of the fragments but also on the maintenance of optimal oral hygiene.